2020
DOI: 10.1021/acs.jpclett.0c00583
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Pseudocapacitance and Faradaic Charge Transfer in High-Mobility Thin-Film Transistors with Solution-Processed Oxide Dielectrics

Abstract: In developing low-power electronics, low-voltage transistors have been intensively investigated. One of the most important findings is that some high-k oxide gate dielectrics can lead to remarkable enhancement of apparent mobility in thin-film transistors (TFTs), which is not clearly understood. Here, we investigate InO x TFTs with solution-processed AlO x dielectrics. At very low frequencies (<1 Hz), the AlO x films feature strong voltage-dependent capacitance. Also, cyclic voltammograms show clear features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…Still, this would yield only one order of magnitude difference in the ON current by itself. In addition to the electric double-layer capacitance, faradaic charge exchanges at the quasi-static frequency levels (Liang et al, 2020b), reflects as several orders of magnitude increase in the capacitance of the MOS capacitor. This can explain the difference in the ON current of the devices observed here, as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, this would yield only one order of magnitude difference in the ON current by itself. In addition to the electric double-layer capacitance, faradaic charge exchanges at the quasi-static frequency levels (Liang et al, 2020b), reflects as several orders of magnitude increase in the capacitance of the MOS capacitor. This can explain the difference in the ON current of the devices observed here, as well.…”
Section: Resultsmentioning
confidence: 99%
“…(Futscher et al, 2020). Residuals in the AlO x dielectrics, such as H + and OH − ions, were reported partly responsible for the enhanced quasi-static frequency polarization in the dielectric (Daunis et al, 2018;Bolat et al, 2020;Liang et al, 2020b). Secondary ion mass spectroscopy (SIMS) measurements were performed on the bilayer dielectrics spin-coated on Si wafers to investigate the hypothesis in detail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective reduction of C ′ in Ar/O 2 plasma‐treated ZAO GIs ascribes the suppression of oxygen‐related defects in the surface and/or bulk of ZAO. [ 48a,49,50 ] Table 1 summarizes all the dielectric properties of ZAO GIs. The areal capacitance and dielectric constant of pristine, 1 and 2 cycles Ar/O 2 plasma‐treated ZAO GIs are 248, 228, and 220 nF cm −2 , and 13.51, 12.35, and 11.96, respectively, at the frequency of 100 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with our observations, previous reports suggested that low‐temperature solution‐processed oxide gate dielectric materials can suffer from increased capacitance at low frequencies due to hydrogen content remaining in the films, [ 52 ] for instance, from incomplete sol–gel densification (MOHM), [ 26 ] leading to slow formation/reorientation of dipole moments and/or proton migration upon application of positive gate voltage. [ 53 ] Therefore, an annealing temperature of 500 °C was selected for further studies of the material. The results highlight the importance of measuring the low‐frequency capacitance after plasma treatment for solution‐processed dielectrics, to avoid mobility overestimation in the case that a plasma treatment is performed before the semiconductor film is processed.…”
Section: Resultsmentioning
confidence: 99%